2017
DOI: 10.3892/mmr.2017.6325
|View full text |Cite
|
Sign up to set email alerts
|

Vatalanib, a tyrosine kinase inhibitor, decreases hepatic fibrosis and sinusoidal capillarization in CCl4-induced fibrotic mice

Abstract: Among the various consequence arising from lung injury, hepatic fibrosis is the most severe. Decreasing the effects of hepatic fibrosis remains one of the primary therapeutic challenges in hepatology. Dysfunction of hepatic sinusoidal endothelial cells is considered to be one of the initial events that occur in liver injury. Vascular endothelial growth factor signaling is involved in the progression of genotype changes. The aim of the present study was to determine the effect of the tyrosine kinase inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Moreover, previous studies have revealed that the relationship between liver fibrosis and endothelial-mediated angiogenesis seriously impedes the reversal and remission of liver fibrosis 13,14. Antiangiogenic therapy might be a strategy for the treatment of hepatic fibrosis and portal hypertension 8,15,16…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have revealed that the relationship between liver fibrosis and endothelial-mediated angiogenesis seriously impedes the reversal and remission of liver fibrosis 13,14. Antiangiogenic therapy might be a strategy for the treatment of hepatic fibrosis and portal hypertension 8,15,16…”
Section: Introductionmentioning
confidence: 99%
“…These observations emphasize the importance of identifying the exact composition of the cytoskeleton ring and molecules involved in membrane fusion. Identification of such a mechanism will also help us to understand how to control fenestrae opening and to design drugs that could slow down the fibrosis progression or promote fibrosis reversion . Indeed, after chronic injury, such as viral hepatitis or alcoholic disorder and nonalcoholic steatohepatitis, the liver develops fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of such a mechanism will also help us to understand how to control fenestrae opening and to design drugs that could slow down the fibrosis progression or promote fibrosis reversion. (20) Indeed, after chronic injury, such as viral hepatitis or alcoholic disorder and nonalcoholic steatohepatitis, the liver develops fibrosis. Fibrosis is a slow process promoting an extracellular matrix accumulation, resulting in a general increase in organ stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…LSECs can synthesize and secrete NO and ET, thereby regulating intrahepatic vasodilation and contraction, and play an important role in regulating hepatic sinus blood flow. NO has a powerful vasodilator effect, which directly stimulates soluble guanylate cyclase in a paracrine form, which increases cyclic guanylate, which causes Ca 2+ reduction and vasodilation [25,26]. Under physiological conditions, LSECs can express endothelial nitric oxide synthase (eNOS) and synthesize NO through eNOS, but the level of NO is low.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%